ПАРСЫША СӨЗЛЕРДЕН ЖАСАЛҒАН АДАМ АТЛАРЫ - Даниярова, З.Ж. (ILIM hám JÁMIYET, 2019)
In the article it is stated, that under the influence of the Persian, then Arabic language there are many words from these languages, and through them from other languages as well. The Persian names from folklore were chosen as the object of the given research. The language of Karakalpak folklore is considered to be an invaluable heritage, reflecting the wisdom of the people and the periods of their historical development. In the lexical layer of Karakalpak folklore there are many borrowings from the Arabic and Persian languages. Antroponyms reflect in the language the history, culture, lifestyle and psychology of the people.